Supervised progressive resistance training in adolescent girls with primary dysmenorrhea - Sufiyan Adam Abdulahi; Dessalegn Wase Mola; Ricardo Ricci Uvinha; Alemmebrat Kiflu Adane; Abdi Gudeta Taye; Tariku Temeche Mare; Md. Hamidur Rahman; Nugroho Susanto; Agam Akhmad Syaukani (Journal of Coaching and Sports Science, 2026)
Background: Primary dysmenorrhea is a gynaecological condition  amongadolescents and is accompanied by depression and anxiety. Although physical activity is recommended as a non-pharmacological strategy, evidence regarding changes following supervised progressive resistance training among adolescents remains limited. Aims: This study aimed to examine changes in depression and anxiety symptoms following an 8-week supervised progressive resistance training program among adolescent girls with moderate-to-severe primary dysmenorrhea in Haramaya Town, Ethiopia. Methods: A one-group pre-test–post-test quasi-experimental design was conducted with 41 adolescent girls aged 15–20 years from public high schools. Participants completed a supervised resistance training program three times weekly for eight consecutive weeks. Depression and anxiety symptoms were assessed using the Beck Depression Inventory-II (BDI-II) and Beck Anxiety Inventory (BAI) during days 1–3 of the menstrual cycle at baseline and during the first post-intervention menstrual cycle. Data were analyzed using Shapiro–Wilk tests, paired-samples t-tests, and Cohen’s dZ for within-participant effect sizes. Result: Significant pre-to-post reductions were observed in both outcomes. Mean BDI-II scores decreased from 32.54 ± 6.86 to 10.44 ± 7.25, t(40) = 16.38, p < .001, dz = 2.56. Mean BAI scores decreased from 33.22 ± 7.16 to 11.66 ± 7.75, t(40) = 19.75, p < .001, dz = 3.08. Descriptively, most participants shifted from moderate-to-severe depression and anxiety categories at baseline to minimal symptom categories after the program. Conclusion: Participation in the 8-week supervised progressive resistance training program was associated with reductions in depression and anxiety symptoms. However, because the study did not include a control group, the findings should not be interpreted as evidence of causality. Supervised progressive resistance training may represent a promising complementary non-pharmacological approach for supporting psychological well-being among adolescents with primary dysmenorrhea.